Beyond industrialization: New approaches to development strategy based on the service sector - Peter Sheehan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Industrialization occupies a central place in the rich tapestry of development theory and practice. Although that place has varied over time, many have agreed with Nicholas Kaldor that the kind of economic growth that leads to high real income per capita can only occur through industrialization. This paper argues that it is becoming increasingly difficult for most developing countries to achieve rapid growth through industrialization, and especially through export oriented activities. But the key mechanisms seen as driving the industrial take-off in much of the literature (internal increasing returns, transfer of labour into higher value activities and pecuniary externalities) are alive and well, and are evident in services as well as in industry. Furthermore, China is actively trying to move from a strategy based on industrialization to one based much more on agriculture and services, as the costs of the current pattern of industrialization become prohibitive, and India has demonstrated that rapid growth based primarily on the services sector is possible. Thus more attention needs to be given to strategies based on the expansion of the agricultural and services sectors, and to the ways in which better services in rural areas and higher rural output can combine to achieve rapid growth and improved human welfare in poor countries.
Keywords: O11; O14; 330; industrialization; services; development strategy; rapid growth; Industrialisierung; Entwicklungstheorie; Entwicklungsstrategie; Dienstleistungssektor; Wirtschaftswachstum; Entwicklungsländer